'Put the wet stuff on the hot stuff': The legacy and drivers of conflict surrounding wildfire suppression. (October 2015) - Paveglio, Travis B.; Carroll, Matthew S.; Hall, Troy E.; Brenkert-Smith, Hannah
Abstract: Existing research demonstrates that wildfire events can lead to conflict among local residents and outside professionals involved in wildfire management or suppression. What has been missing in the wildfire literature is a more explicit understanding of the social dynamics that influence such conflict in rural or agricultural communities and their long-term legacy for future wildfire management. Authors conducted interviews with local residents of a southeastern Washington community in 2012 to better understand conflict surrounding management of the 2006 Columbia Complex Fire. We utilize structuration theory to demonstrate how conflict stemmed from differences in the norms characterizing the local community and the established practices of outside firefighters, the inability of these two populations to communicate in a way that established shared meanings for values at risk, and local residents' desire to contribute to suppression efforts rather that give up complete control to outside resources. The legacy of conflict during the Columbia Complex fire included increased distrust of externally based fire response and entrenched views about locals' right to protect their property. We conclude by discussing the need to account for the legacy of conflict during future wildfire events and the reasons such conflict are likely in rural or agricultural communities. Highlights: We explore the causes and legacy of rural conflict over wildfire management. Structuration theory is used to advance understanding about wildfire conflict. Conflict arose from incongruities in firefighting and rural community culture. Incongruities included prioritization of values at risk and locals' access. Conflict from previous fires persists and will influence future wildfire response.